1999
DOI: 10.1016/s0002-9440(10)65090-0
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelium, Hemodynamic Forces, and Atherogenesis

Abstract: Intimal lipid accumulation, hyperplasia, and scarring are stigmata of atherosclerotic vascular disease, whose major complications-myocardial and cerebral ischemia and infarction-continue to be major health problems in developed nations. 1 This insidiously progressive disease typically spans decades, but can reach a clinical horizon in a matter of minutes due to critical changes in a given atherosclerotic plaque that result in localized but lifethreatening thrombosis. Epidemiological studies have established th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
123
0
11

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(136 citation statements)
references
References 38 publications
2
123
0
11
Order By: Relevance
“…Moreover, it is now established that IH does not occur randomly throughout the circulatory system, but occurs much more frequently near arterial bifurcations and in areas of high vessel curvature (Gimbrone, 1999). IH is strongly associated with disturbed haemodynamic characteristics, such as flow detachment from the arterial wall, flow recirculation and oscillatory flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is now established that IH does not occur randomly throughout the circulatory system, but occurs much more frequently near arterial bifurcations and in areas of high vessel curvature (Gimbrone, 1999). IH is strongly associated with disturbed haemodynamic characteristics, such as flow detachment from the arterial wall, flow recirculation and oscillatory flow.…”
Section: Introductionmentioning
confidence: 99%
“…In linear sections of the vasculature with steady laminar flow and relatively high wall shear stress (greater than 1 Pa), EC are well aligned in the direction of flow and cell-cell junctions are tight (Gimbrone, 1999). As a consequence, the endothelium is a highly stable cell population, with a very low rates of proliferation and death (Davies, 2000), and low permeability to blood-borne macromolecules, such as LDLs (Schachter, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Perturbed shear stress alone or high shear stress associated with other classical risk factors of atherosclerosis may trigger signal transduction events that in turn may lead to endothelial dysfunction and enhanced atherogenesis (2)(3)(4). It has been demonstrated that areas highly prone to atherosclerosis have unique patterns of disturbed flow, characterized by regions of flow separation, recirculation, and temporal and spatial gradients of shear stress (4).…”
mentioning
confidence: 99%
“…NO controls vascular oxidative stress and the expression of redox-regulated genes (13,14). Evidence exists that eNOS activity is reduced at sites of perturbed shear stress (2,(5)(6)(7)(8)11).…”
mentioning
confidence: 99%
“…After 15 min to 1 h, FAK and c-Jun N-terminal kinase (JNK) are activated, at least in culture systems (12). Later, transcription factors will be activated to alter gene expression (2,13,14) and, with time, to modulate endothelial cell phenotype, cell adhesion, and even atherogenesis (2,14). The mechanisms mediating these effects, especially the key initiating mechanosensing molecule, remain largely unknown.…”
mentioning
confidence: 99%